A Feasbility study on Second Phase of the Burgos Wind farm - Maluenda, Jo-Ann (College of Engineering, 2001)
The Second Phase of Burgos Wind Farm is located in Burgos, llocos Norte. The second phase project, composed of 56 wind turbines with total capacity of 42 MW will be installed. The power generated by the proposed wind farm will be connected to the national electric grid. Thus, it will augment the supply of the power consumption needs of grid-connected areas. Given that Luzon, Visayas and Mindanao are already grid-connected, then, the power contribution of the wind farm in terms of power generation can now be determined as a percentage of the total electricity requirements of the whole Philippines. This venture will be connected via 115 kV transmission lines to the national grid. Therefore, all areas connected to the national grid will be supplied with its electricity. The electricity demand projections for the Philippines for years 2001 to 2010 as forecasted by the Department of Energy are outlined in the current Philippines Energy Plan and used by the group. For supply projections, the total electrical capacity for the past ten years was tabulated by adding up all existing capacity of power plants in the Philippines and then forecasted using the appropriate forecasting technique. The group is confident that this venture can compete with other technologies due to its use of indigenous resources, low maintenance costs, environmental benefits, passage of the Power Bill and the anticipated power shortage in 2004. Market share was determined to be 31% for the first year, 3% for 2003, 2%, 1.408%, 1.05, 0.793%, 0.606%, 0.473% and 0.375% for the succeeding years. For the marketing strategy, product, pricing, placement and promotions strategies were determined. The venture name is Second Phase of the Burgos Wind Farm priced at P2/kWh. The electricity will be sold to distributors like Meralco, local government-owned distribution centers and electric cooperatives nationwide. For promotions, a movement aimed at educating consumers about where their power comes from and how they can identify - and purchase - power from renewable sources will be the basis for the marketing plan designed for the end-users. It will use a combination of factual and emotional marketing factors to influence consumers to purchase the electricity. The target audience will be potential investors, end-users and students. The production will stay constant at 116 GWh per year. The Second Phase wind farm will be under the surveillance of a supervisor which oversees the daily operations. His tasks include deciphering the data that is being transmitted by the wind turbines. His staff is composed of 1 mechanical engineer and 2 electrical engineers. The wind farm must be monitored round the clock; therefore one day will encompass three shifts. The project site was chosen to be in Saoit, Burgos with a lot size of 320 hectares. This has been decided through thorough evaluation. The total project cost to start the venture is Php 1,707,491,884.00 A one-month pre-operating cost was used. Approximately Php 1.6B will be financed by Japan Bank of International Cooperation. The loan will be paid in 40 years, 5 year grace period and interest of 1% per annum. Financial statements like the income statement, cash flow projections and balance sheet for the operating period of 2002 to 2010 were generated. The cash flow projections indicate a positive net cash flow for the operating period. It can be sent that the same positive trend is present in the income statement. From the financial analysis, the financial ratios show a stable financial and profitable position for the venture in the next 9 years. The ratios show that the venture is in the black through the operating period. The test for liquidity shows an increasing trend therefore this indicates a strong assurance that a venture will be able to meet its obligations. The tests of Debt Service have decreasing trends during and after the grace period of 5 years. This signifies greater protection for JBIG. The decreasing Fixed Assets to Net Worth ratio signifies that the liquid of the net worth is increasing hence more of the capital of the venture becomes available of liquidation occurs. The net turnover ratio observes a fluctuating trend. This is due to the grace period set by JBIG and the lack of increase in production capacity. Note that this feasibility study is only concerned with the Second Phase of the Burgos Wind Farm and is constrained by limitations set by PNOC. The production capacity can be increased but this will need another feasibility study. Hence, the net turnover computed above can be changed. The decreasing trend of the asset turnover shows that the capital is being used less frequently during the years. The decreasing return on net operating profit presents that the total tangible assets increases through the years. The return on assets experiences a decreasing trend; this indicates that PNOC's share of the year's operation as related to resources invested decreases over the years. The high Debt Coverage ratio shows that the venture's ability to cover its debt becomes greater through the years. The payback period was computed to be 8.04 years, thus the venture will be able to gain back its investment after the said period. The sensitivity analysis shows that the venture returned a positive NPV of P685,494,050 and an IRR of 135%, which is significantly higher than the MARR of 30%, Both of these indicate that the venture is an acceptable business project. This venture will be spearheaded by PNOC-EDC (Energy Development Gorporation). The company will hire the following for the on-site maintenance and supervision of the project: 1 maintenance supervisor, 1 mechanical engineer, 1 senior electrical engineer, 1 junior electrical engineer. They will be given basic salary according to their qualifications, plus benefits like SSS, Medicare and 13th month pay. In the social profitability analysis, it has shown that there are a lot of benefits arising from the venture. It has generated various quantitative benefits such as the generation of income-generating jobs, added revenue to the government in terms of taxes, and the net savings from the avoided oil importation. The qualitative aspects of the project include substantial reductions in the amount of CO2 emission and its role in attaining the objectives of ensuring a sustainable development in the Philippines as well as the attainment of the energy self-sufficiency target mapped out by the government until the year 2025. The only probable drawbacks of the project is the potential disturbance of the community located near the site but it has also been shown that this can be mitigated and that initial computations for the anticipated noise level in the area are below the accepted level established in Europe. From the analysis of the quantitative and qualitative benefits and drawbacks, the benefits outweigh the drawbacks significantly. Therefore it can be concluded that the project is socially feasible. In all aspects of the study, the project was proven to be FEASIBLE.